1990
DOI: 10.1007/bf00156776
|View full text |Cite
|
Sign up to set email alerts
|

Particle beams as a source of noise storm depression?

Abstract: The February 5, 1986 flare-related radio continuum depression is studied, compared with other noise storm depression events and discussed in the framework of current type I storm models. The influence of flare plasma flow or shocks and of superthermal electrons on noise storm radiation is considered. The presence of fast drifting emission features just before and during the decrease of the intensity, the association between the depression onset and the microwave burst maximum, the simultaneous appearance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…These events probably belong to the category of picoflares mentioned earlier. The possibility of fluctuations in the amplitude of the type I bursts in Figures 1 and 2 as well as the other events in Table 1, due to either a screening of the radio source region (by hot and dense evaporated chromospheric material) in the aftermath of flare onset as pointed out by Böhme & Krüger (1982), Aurass et al (1990), and Zaitsev et al (1994 or formation/deformation of reconnection regions (from where the type I emission is generated) after/before CMEs as shown by Chertok et al (2001) and Iwai et al (2012), can be ruled out since the events reported in the present work were not accompanied by either CMEs or Hα/X-ray flares, as mentioned earlier. We verified this using the previously mentioned online resources 3 and the SGD reports.…”
Section: Results and Analysismentioning
confidence: 90%
“…These events probably belong to the category of picoflares mentioned earlier. The possibility of fluctuations in the amplitude of the type I bursts in Figures 1 and 2 as well as the other events in Table 1, due to either a screening of the radio source region (by hot and dense evaporated chromospheric material) in the aftermath of flare onset as pointed out by Böhme & Krüger (1982), Aurass et al (1990), and Zaitsev et al (1994 or formation/deformation of reconnection regions (from where the type I emission is generated) after/before CMEs as shown by Chertok et al (2001) and Iwai et al (2012), can be ruled out since the events reported in the present work were not accompanied by either CMEs or Hα/X-ray flares, as mentioned earlier. We verified this using the previously mentioned online resources 3 and the SGD reports.…”
Section: Results and Analysismentioning
confidence: 90%
“…Type-I bursts are usually associated with active regions. They are sometimes enhanced or modulated by flares and CMEs (Aurass et al 1990(Aurass et al , 1993Chertok et al 2001;Iwai et al 2012a). The emissions of type-I bursts are usually sporadic (less than 1 s) and the emission is O-mode (e.g., Krucker et al, 1995).…”
Section: Growth Rate Of the Type-i Burstmentioning
confidence: 99%
“…No flares larger than C class (Watanabe et al 2012) or coronal mass ejections (CMEs) were reported during the observational periods on January 16 and 26 1 . Hence, the type-I modulation by flares (Aurass et al 1990(Aurass et al , 1993 or CMEs (Chertok et al 2001;Iwai et al 2012a) can be neglected. A CME was observed during the observational period on January 23.…”
Section: Introductionmentioning
confidence: 99%
“…While these storms are known to occur over very long timescales (e.g. Del Zanna et al 2011), they have also been observed to react rapidly to flare and coronal mass ejection (CME) activity (Aurass et al 1990;Kathiravan et al 2007;Iwai et al 2012).…”
Section: Introductionmentioning
confidence: 99%